A Comprehensive Literature Survey on The New Emerging Technologies in Education - Mayank Sharma; Ramakant Sharma (AG Volumes, 2022)
The education industry has been way overdue to accept digital developments. The newest educational technology developments offer a pleasant shift. Since the epidemic transferred learning from the classroom to homes, people have observed new modes of schooling. Innovative advancements in educational technology give opportunity to address expanding education demands. Solutions including online courses give a mechanism to keep lessons running, and trends such as augmented reality as well as immersive learning are crucial to harness growth and upgrade the learning experience. Since the pandemic rendered distant learning compulsory, it gave a unique chance to embrace digital trends which can adapt as well as transfer over to in-person training. The developing trends in the educational technology emphasize on connection, adaptability and student-centered learning.